Utilisation of medications among elderly patients in intensive care units: a cross-sectional study using a nationwide claims database - Sun-Young Jung; Hyun Joo Lee (BMJ Open)
Objectives Clinical practice guidelines for the management of pain and sedation in critically ill patients have been developed and applied; however, there is limited data on medication use among elderly patients. This study identifies current practice patterns for analgo-sedative use in mechanically ventilated elderly patients in Korea using a national claims database.Design Cross-sectional study.Setting and participants Ventilated elderly patients aged 65 years or older in intensive care units (ICUs) from an aged patients’ national claims database in KoreaPrimary outcome measures Use of sedatives including benzodiazepines, opioids and non-opioid analgesics, neuromuscular blocking agents (NMBAs) and antipsychotic drugs were analysed by the duration of mechanical ventilation (MV), age and time.Results From 2012 to 2016, 22 677 elderly patients underwent MV in 267 general or tertiary ICUs. Mean age was 77.2 (±6.9) years and the median duration of MV was 4.1 days; 77.2% of patients received sedatives, 65.0% analgesics, 29.1% NMBAs and 19.6% antipsychotics. Midazolam (62.0%) was the most commonly prescribed medication. The proportions of sedatives, analgesics and NMBAs increased, whereas the percentages of person-days decreased with longer MV duration (p<0.01). With advanced age, the prevalence and duration of sedative, analgesic and NMBA use decreased (adjusted OR (95% CI) 0.98 (0.97 to 0.98) in all three classes) while antipsychotic did not (adjusted OR 1.00 (1.00–1.01)). Annually, benzodiazepines showed reduced administration (76.2% in 2012 and 71.4% in 2016, p<0.01), while daily opioid dose increased (21.6 in 2012 vs 30.0 mg in 2016, p<0.01).Conclusions The prevalence of sedative, analgesic and NMBAs use and daily opioid doses were lower, whereas antipsychotic use was higher compared with those in previous studies in adult patients. The findings warrant further studies investigating appropriateness and safety of medication use that consider clinical severity scores with a focus on elderly patients in ICUs.